Kondisi Tubuh dan Jiwa Setelah Kematian dalam Filsafat Mulla Shadra dan Al-Ghazali - Lufi Nurfadhilah (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The purpose of this research is to examine the thoughts of Mulla Shadra and al-Ghazali on a condition of body and soul after death. This paper is a literature study, using qualitative methods, and Islamic philosophy as an umbrella theory. The findings in this study are that both offer each other three concepts of physical resurrection and there are differences in views on Mulla Shadra and al-Ghazali regarding physical resurrection. On the basis of this, the researchers concluded that body and soul will be resurrected after death according to Mulla Shadra and al-Ghazali and the resurrected body is the old body which is material according to al-Ghazali, while for Mulla Shadra it is the new immaterial body which is the imagination of the human psyche.